Relieving ammonia inhibition by zero-valent iron (ZVI) dosing to enhance methanogenesis in the high solid anaerobic digestion of swine manure - Meng, Xiaoshan (Waste management (New York, N.Y.), 2020)
Copyright © 2020 Elsevier Ltd. All rights reserved.